Perception of nurses about self-care in front of the complications of diabetes in the quality of life (Research, Society and Development, 2020)
DM can negatively affect physical well-being as a result of acute and chronic complications, as well as treatment needs after the onset of DM in the individual, he has significant chances of aggravating problems over the years, in contrast self-care can bring benefits to those affected by recovering QOL. With the objective of analyzing through the study of articles the benefits that self-care brings in the prevention of complications that diabetes mellitus causes in the quality of life in the view of nurses, being an integrative review of the literature with a qualitative approach. Diabetes Mellitus has a significant physical and emotional impact, culminating in a decrease in the autonomy and self-confidence of these individuals, causing their perception of themselves to be altered, seeing themselves as incapable of fulfilling their goals and social participation decreases considerably with the over the years due to the greater impairment of the disease. It was observed that actions involving health education are fundamental for people to be successful in controlling the disease, either through greater adherence to treatment or through the implementation of necessary changes in their existing habits, which can extend the quality of life with quality.Incluir o resumo em inglês.